2006
DOI: 10.1089/jpm.2006.9.437
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disturbance in Supportive Care of Cancer: A Review

Abstract: Insomnia constitutes a significant source of suffering for patients with cancer as they move through the course of treatment and advanced illness. Practicing physicians and caregivers are challenged to address this troubling symptom without the benefit of an extensive literature specific to this population. There is evidence to suggest that the routine clinical management of patients with cancer with insomnia is discordant with best practices documented in the available literature. This paper reviews the liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 121 publications
1
55
0
Order By: Relevance
“…One of the major goals of palliative medicine in cancer is to control symptoms that may interfere with patients' quality of life (QoL). Insomnia, defined as a subjective complaint of inadequate nocturnal sleep, is the most common sleep disorder reported by cancer patients [9,14]. Insomnia in the setting of cancer is defined differently by individual patients as a disruption of previous sleep patterns, difficulty falling asleep, frequent waking, nonrestorative sleep, or some combination of the above [14].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…One of the major goals of palliative medicine in cancer is to control symptoms that may interfere with patients' quality of life (QoL). Insomnia, defined as a subjective complaint of inadequate nocturnal sleep, is the most common sleep disorder reported by cancer patients [9,14]. Insomnia in the setting of cancer is defined differently by individual patients as a disruption of previous sleep patterns, difficulty falling asleep, frequent waking, nonrestorative sleep, or some combination of the above [14].…”
Section: Introductionmentioning
confidence: 99%
“…Insomnia, defined as a subjective complaint of inadequate nocturnal sleep, is the most common sleep disorder reported by cancer patients [9,14]. Insomnia in the setting of cancer is defined differently by individual patients as a disruption of previous sleep patterns, difficulty falling asleep, frequent waking, nonrestorative sleep, or some combination of the above [14]. Currently, the pathophysiology of insomnia is ill-defined, and it is likely to be underreported by patients [14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to , cited in Hayne, 2002, in a search for a cure, biomedical experts have searched for scientific knowledge, and in doing so they have come to define healing in terms of logical and "rationalistic factors" (p. There is a vast body of knowledge that has shown that a diagnosis and treatment of cancer brings to the forefront a host of difficulties that threaten the physical, psychological, and emotional well being of the cancer patient. For example, pain, financial burden, anxiety, sleep disturbances, fatigue, nausea, appetite disturbances, hair loss, depression, and fear, among others are well-documented findings in the empirical literature on the impact of cancer on the patient (Chochinov, 2001;Graci, 2005;Herrstedt, 2002;Kayl & Meyers, 2006;Kvale & Shuster, 2006;Richardson, 1995;Rosman, 2004;Visser & Smets, 1998;Wright, Kiely, Lynch, Cull & Selby, 2002).…”
Section: Cancermentioning
confidence: 99%